(untitled) (Mustansiria Dental Journal, 2018)
The aim of this study was to compare apical microleakage of MTA following reverse retrograde root filling with that following Alumina Cement, Light Cement, Zenium HMP retrofilling. The root canals of 42 extracted teeth were instrumented and obturated with vertically condensed gutta-percha. Each tooth was apically resected and the apex was prepared by fissure bur to 2 mm depth and the root surface isolated with nail varnish. Teeth were divided randomly into four groups of 10 teeth each. First group was retrofilled with MTA, second group with Alumina Cement, third group with Light Cement, and the fourth group with Zenium HMP. Following immersion in 2% Fuchsine dye for 72 hours, the roots were sectioned and the depth of dye penetration was evaluated by a Global stereomicroscope at x70 magnification.The sealing effectiveness of the retrograde filling materials was determined by their ability to inhibit dye penetration. Results showed that the least leakage for zeniuum HMP cement with a mean of 0.6, MTA with a mean of 1.0, light cement with a mean of 1.10, alumina cement with a mean of 1.50 with the most leakage. However, these differences were not seen to be statistically significant using the Kruskal Wallis Test or the Mann Whitney Test. It was concluded that Zenium HMP cement provides a better seal than MTA and Light Cement and Alumina Cement when used as retrograde filling.